Supervielle, Jules. Les amis inconnus/Unknown Friends. Trans. Philip Cranston. Potomac, MD: Scripta Humanistica, 2008. xiii + 217 pp. $69.95. ISBN 1–882528–53–0. (Forum for Modern Language Studies, 2010)
The article reviews the book "Les amis inconnus/Unknown Friends," by Jules Supervielle, translated by Philip Cranston.